Improving Skill in Writing Inspirational Story Text in Quantum Learning using Comics - Haris, M. Alfan; Hasanudin, Cahyo; Sutrimah, Sutrimah; Fitrianingsih, Ayu (IKIP PGRI Bojonegoro, 2025)
This study was conducted because difficulties to write inspirational story text were found by students in Ninth grade of SMP SMP Plus Maulana Malik Ibrahim. It was caused by less of understanding related to the structure of inspirational story text. This study aimed to explore the improvement of students’ skill in writing inspirational story text in quantum learning using comics. This study was classroom action researchwhich was conducted in two cycles. Each cycle had four stages, namely planning, acting, observing, and reflecting. Results of study showed that in pre-treatment, students’ average scores were 53 with classical completion rate of 14,28%. In cycle I, students’ average scores were improved to be 72 with classical completion rate of 66,6%. Moreover, in cycle II, it was improved to be 84 with classical completion rate of 90,4%. It could be concluded that students’ skill in writing inspirational story textwas improved after being taught using comics as media in quantum learning.